The Legality of Divorce in Aceh: A Study of Divorce Practices Out of Religious Courts - Azwir Azwir; Pagar Pagar; Muhammad Syukri Albani Nasution (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2022)
Divorce for the people of Aceh is inseparable from Islamic law, the power of Islamic law dominates in every legal decision related to religion. Islamic law for the people of Aceh is understood as fiqh produced by the ulama (Muslim scholars). Likewise with divorce, when there are legal differences, Islamic law becomes the main priority in resolving these differences. This study aims to analyze the legality of divorce for the people of Aceh between Islamic law and state law. In addition, this paper will also analyze the legal trends used by the Acehnese people in divorce cases. This paper is empirical legal research with a statute approach and the sociology of law, the primary data source interviews, this research also examines essential writings related to divorce. The results show that the legality of divorce for the majority of the people of Aceh is what is specified in the Syafi'i school of jurisprudence, state law will be used if needed for administrative needs, but people who are aware of the legality of state law, will use the judiciary in divorce cases to guarantee post-divorce rights.